1997
DOI: 10.1073/pnas.94.8.3866
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal deletion mutant of pokeweed antiviral protein inhibits viral infection but does not depurinate host ribosomes

Abstract: Pokeweed antiviral protein (PAP), a 29-kDa protein isolated from Phytolacca americana, inhibits translation by catalytically removing a specific adenine residue from the large rRNA of the 60S subunit of eukaryotic ribosomes. In addition to its ribosome-inactivating ability, PAP has potent antiviral activity against many plant and animal viruses, including HIV. We recently described the isolation and characterization of nontoxic PAP mutants, NT123-2, which has a point mutation (E176V) in the active site that ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 22 publications
4
91
0
1
Order By: Relevance
“…In vitro depurination of capped and uncapped RNAs by PAP+ BMV RNAs (500 ng) (A) or capped (B) or uncapped (C) luciferase transcripts (500 ng) were incubated with increasing concentrations of PAP, 10 pg (3+3 pM), 5 ng (1+65 nM), or 100 ng (33+3 nM), in a total volume of 100 mL for 30 min at 30 8C+ Following incubation, RNAs were precipitated and divided in half+ Half was treated with aniline (ϩ), the other half was not (Ϫ)+ Each RNA was separated on a 7 M urea/6% polyacrylamide gel and visualized with ethidium bromide+ Arrows indicate the four full-length BMV RNAs of 3+2, 2+8, 2+1, and 0+8 kb (A) and the single 1-kb capped and uncapped luciferase transcripts (B and C)+ plates+ Translation inhibition was overcome by treating BMV RNAs with PAP in the presence of increasing concentrations of the cap analog, m7GpppG, indicating that PAP recognizes the m7GpppN (where N is any nucleotide) cap on the BMV RNAs+ It is unlikely that a cap binding activity copurified with PAP and PAP mutants and is responsible for these observations, as purified proteins were homogeneous by SDS-PAGE analysis )+ In addition, the different PAP proteins showed different levels of translation inhibitory activity on capped RNA templates (PAP and PAPn inhibited translation to a similar extent, PAPx had no inhibitory effect, and PAPc had an intermediate effect), and the concentrations that inhibited translation correlated well with those that depurinated the RNA templates+ Using a highly sensitive primer extension assay, we show here that PAP depurinates both reticulocyte lysate and tobacco ribosomes+ The classic method used to monitor depurination relies upon ethidium bromide staining of denaturing polyacrylamide gels, and may not be sensitive enough to detect low levels of depurination+ We used the more sensitive primer extension assay and did not detect any depurination activity by the nontoxic PAP mutants, PAPn or PAPc+ In contrast, wild-type PAP depurinated both reticulocyte lysate and tobacco ribosomes by removing more than one adenine (A4324 and A4321) and a guanine (G4323)+ Similar results were also observed with yeast ribosomes (data not shown)+ The removal of this guanine residue from the S/R loop following treatment with ricin has been reported previously (Endo & Tsurugi, 1986;Endo et al+, 1987)+ However, investigations of rRNA depurination by RIPs typically report the loss of only one adenine (A4324), largely because detection methods rely on the depurination of A4324 as a defining characteristic of RIPs Prestle et al+, 1992)+ These results demonstrate that PAP is capable of removing multiple adenines and a guanine from the rRNA+ In agreement with these results, Barbieri et al+ (1997) quantified the release of adenine from rRNA treated with PAP and concluded that the RNA template is depurinated at multiple sites+ More recently, adenine and guanine residues have been shown to be released from HIV-1 RNA and E. coli rRNA following incubation with PAP in vitro (Rajamohan et al+, 1999)+ We previously reported that expression in tobacco of PAPc inhibited viral infection, suggesting that the antiviral activity of PAP is not due to depurination of host ribosomes (Tumer et al+, 1997)+ The nontoxic PAPn also inhibited viral infection when expressed in transgenic plants (Zoubenko et al+, unpubl+ data)+ PAP expressed in yeast specifically inhibited Ty1 retrotransposition, but not the L-A and M 1 -dependent killer virus phenotype, indicating that PAP has viral RNA-specific effects in vivo (Tumer et al+, 1998)+ The hypothesis that PAP ma...…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In vitro depurination of capped and uncapped RNAs by PAP+ BMV RNAs (500 ng) (A) or capped (B) or uncapped (C) luciferase transcripts (500 ng) were incubated with increasing concentrations of PAP, 10 pg (3+3 pM), 5 ng (1+65 nM), or 100 ng (33+3 nM), in a total volume of 100 mL for 30 min at 30 8C+ Following incubation, RNAs were precipitated and divided in half+ Half was treated with aniline (ϩ), the other half was not (Ϫ)+ Each RNA was separated on a 7 M urea/6% polyacrylamide gel and visualized with ethidium bromide+ Arrows indicate the four full-length BMV RNAs of 3+2, 2+8, 2+1, and 0+8 kb (A) and the single 1-kb capped and uncapped luciferase transcripts (B and C)+ plates+ Translation inhibition was overcome by treating BMV RNAs with PAP in the presence of increasing concentrations of the cap analog, m7GpppG, indicating that PAP recognizes the m7GpppN (where N is any nucleotide) cap on the BMV RNAs+ It is unlikely that a cap binding activity copurified with PAP and PAP mutants and is responsible for these observations, as purified proteins were homogeneous by SDS-PAGE analysis )+ In addition, the different PAP proteins showed different levels of translation inhibitory activity on capped RNA templates (PAP and PAPn inhibited translation to a similar extent, PAPx had no inhibitory effect, and PAPc had an intermediate effect), and the concentrations that inhibited translation correlated well with those that depurinated the RNA templates+ Using a highly sensitive primer extension assay, we show here that PAP depurinates both reticulocyte lysate and tobacco ribosomes+ The classic method used to monitor depurination relies upon ethidium bromide staining of denaturing polyacrylamide gels, and may not be sensitive enough to detect low levels of depurination+ We used the more sensitive primer extension assay and did not detect any depurination activity by the nontoxic PAP mutants, PAPn or PAPc+ In contrast, wild-type PAP depurinated both reticulocyte lysate and tobacco ribosomes by removing more than one adenine (A4324 and A4321) and a guanine (G4323)+ Similar results were also observed with yeast ribosomes (data not shown)+ The removal of this guanine residue from the S/R loop following treatment with ricin has been reported previously (Endo & Tsurugi, 1986;Endo et al+, 1987)+ However, investigations of rRNA depurination by RIPs typically report the loss of only one adenine (A4324), largely because detection methods rely on the depurination of A4324 as a defining characteristic of RIPs Prestle et al+, 1992)+ These results demonstrate that PAP is capable of removing multiple adenines and a guanine from the rRNA+ In agreement with these results, Barbieri et al+ (1997) quantified the release of adenine from rRNA treated with PAP and concluded that the RNA template is depurinated at multiple sites+ More recently, adenine and guanine residues have been shown to be released from HIV-1 RNA and E. coli rRNA following incubation with PAP in vitro (Rajamohan et al+, 1999)+ We previously reported that expression in tobacco of PAPc inhibited viral infection, suggesting that the antiviral activity of PAP is not due to depurination of host ribosomes (Tumer et al+, 1997)+ The nontoxic PAPn also inhibited viral infection when expressed in transgenic plants (Zoubenko et al+, unpubl+ data)+ PAP expressed in yeast specifically inhibited Ty1 retrotransposition, but not the L-A and M 1 -dependent killer virus phenotype, indicating that PAP has viral RNA-specific effects in vivo (Tumer et al+, 1998)+ The hypothesis that PAP ma...…”
Section: Discussionmentioning
confidence: 98%
“…To observe a direct effect of wild-type PAP on viral RNA and mRNA, BMV RNAs and capped and uncapped luciferase transcripts were incubated with increasing concentrations of PAP prior to their separation on an acrylamide denaturing gel+ RNAs (500 ng) were incubated in RIP buffer with 10 pg (3+33 pM), 5 ng (1+65 nM), or 100 ng (33+3 nM) of wild-type PAP at 30 8C for 30 min in a total volume of 100 mL+ RNA incubated in the absence of PAP served as a negative control+ Following incubation, PAP was removed from the mixture by phenol:chloroform extraction, and the treated RNA was divided in half+ Half was incubated with aniline as described in Tumer et al+ (1997)+ Both aniline-treated and -untreated samples were solubilized in formamide buffer, separated on a 7 M urea/6% polyacrylamide gel, and stained with ethidium bromide+…”
Section: Rna Depurination Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Duggar and Armstrong [33] have observed that a protein from P. americana possessed an antiviral activity, and inhibited transmission of tobacco mosaic virus (TMV) in plants; though, not until 1978 PAP was accepted as an inhibitor of protein synthesis [25]. While the mechanism of PAP antiviral activity is somewhat unclear, recent findings, produced by the Hudak and Tumer laboratories, show that this activity is not dependent exclusively on inactivation of ribosomes [34,35]. It has been postulated that a direct interaction of PAP with viral RNA (or DNA) is an alternative antiviral mechanism in play.…”
Section: Activities Attributed To Papmentioning
confidence: 99%
“…Elimination of the N-glycosidase activity of PAP (by site-directed mutagenesis) abolishes antiviral activity [38]. Furthermore, the ability to prevent viral infection of pokeweed leaves by addition of exogenous RIP is dependent on the ability of the added RIP to depurinate pokeweed ribosomes [39].…”
Section: Pap Heat Treatment Of Pap Eliminates Dnase Activity But Notmentioning
confidence: 99%